Penerapan metode Quality Function Deployment dan analisis SWOT sebagai upaya pengembangan bisnis Coffee Shop Hako Gorontalo - Rasyid, Abdul; Wolok, Eduart; Mamonto, Jessica Gabriani (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
HAKO Gorontalo is a Coffee Shop located in Gorontalo City. Along with the increase in coffee shops in Gorontalo City, HAKO experienced a significant decline in income due to increasingly fierce business competition. To face increasingly fierce competition, HAKO Gorontalo needs to develop its business. This research aims to find out the attributes that customers want and to provide suggestions in efforts to develop the HAKO Gorontalo coffee shop business. The method used in this research is the Quality Function Deployment (QFD) method and SWOT Analysis. Based on the results of this research, 5 attributes were found that were deemed unsatisfactory out of 24 attributes obtained based on customer desires. Based on the results of the SWOT analysis, the results show that the HAKO coffee shop is in quadrant one or the progressive quadrant. By using the S - O strategy, it is hoped that the HAKO coffee shop can continue to develop its business. Customer satisfaction surveys conducted periodically can also help to find out the hopes and desires of HAKO Gorontalo coffee shop customers.